Utilization of degraded lands/habitats and poor quality water for livelihood security and mitigating climate change - Dagar, J.C. (Indian Journal of Agroforestry, 2020)
About 2 billion ha in the world is affected by various forms of human induced land degradation with erosion by water being the chief contributor. In India, out of 120.8 million ha (Mh) degraded land, 82.6 Mh is estimated to suffer with water erosion, 24.7 Mh from chemical degradation, 12.4 Mh due to wind erosion and 1.1 Mh from physical (mainly due to stagnation of water) degradation. About 6.73 Mh area is salt-affected. With developing scenarios of severe water scarcity and competition from other sectors of economy, it appears axiomatic that agriculture would have to increasingly depend upon marginal and poor quality waters only. In Canal Command areas alone more than 2.5 Mh area have already become waterlogged and 3.3 Mh salt-affected. To meet various diverse needs of ever-increasing human (more than 1 billion) and animal (484.3 million) population, we would have to rehabilitate all kinds of the problem lands. Many species of trees, shrubs, forbs and grasses can grow well in problematic areas which may not be fit for arable crops. Many of these lands can be reclaimed by adopting alternate land use practices. The sloping and ravine lands can successfully be brought under grass and tree cover selecting suitable erosion resistant species which in turn may also be utilized for fodder and fuel-wood. To check wind erosion sand dunes can be stabilized with stress tolerant vegetation. Vast tracts of arid and semi-arid areas remain barren due to salinity or water scarcity. The salt-affected lands (sodic/alkaline and saline) constrain plant growth owing to the osmotic effects of salt, poor physical conditions leading to poor aeration, nutrition imbalances and toxicities. With use of appropriate planting techniques and salt-tolerant species these can be brought under viable vegetation cover. Auger-hole technique on sodic soils, furrow technique of tree plantation on saline soils, and ridge plantation in waterlogged fields have been found quite appropriate. Further, in most of the arid and semi-arid regions the ground water aquifers are saline. The groundwater surveys indicate that poor quality water utilized in different states of India ranges between 32 and 84% of the total ground water development. Usually cultivation of conventional arable crops with saline irrigation has not been sustainable. Concerted research efforts have shown that by applying appropriate planting and other management techniques (e.g. sub-surface planting and furrow irrigation), the degraded lands (including calcareous) can be put to alternative uses, where salt-tolerant forest and fruit trees, forage grasses, medicinal and aromatic and other high value crops can be equally remunerative. The problem of waterlogging and secondary salinisation can be tackled through sub-surface drainage, which is costly and inherits environmental problems. Biodrainage using fast growing trees like cloned Eucalyptus (known for high transpiration rate) can effectively be used to combat the problem.Tree-based technologies have additional environmental benefits including carbon sequestration, biological reclamation and mitigating climate change. Due to agroforestry movement it has been found that half of the agricultural land in the world has more than 10% tree cover. Some opportunities for alternate land uses through agroforestry systems on problematic areas including eroded, salty and water scarcity and water logged areas have been discussed in this paper.